Causes of Early Age Cracking on Concrete Bridge Deck Expansion Joint Repair Sections. (17th March 2014) - Wright, Jared R.; Rajabipour, Farshad; Laman, Jeffrey A.; Radlińska, Aleksandra
Abstract : Cracking of newly placed binary Portland cement-slag concrete adjacent to bridge deck expansion dam replacements has been observed on several newly rehabilitated sections of bridge decks. This paper investigates the causes of cracking by assessing the concrete mixtures specified for bridge deck rehabilitation projects, as well as reviewing the structural design of decks and the construction and curing methods implemented by the contractors. The work consists of (1) a comprehensive literature review of the causes of cracking on bridge decks, (2) a review of previous bridge deck rehabilitation projects that experienced early-age cracking along with construction observations of active deck rehabilitation projects, and (3) an experimental evaluation of the two most commonly used bridge deck concrete mixtures. Based on the literature review, the causes of concrete bridge deck cracking can be classified into three categories: concrete material properties, construction practices, and structural design factors. The most likely causes of the observed early-age cracking were found to be inadequate curing and failure to properly eliminate the risk of plastic shrinkage cracking. These results underscore the significance of proper moist curing methods for concrete bridge decks, including repair sections. This document also provides a blueprint for future researchers to investigate early-age cracking of concrete structures.